The Improper Use of Country-by-Country Reports: Some Concerns on the Brazilian Approach to BEPS Action 13 - Borges, Alexandre Siciliano; Takano, Caio Augusto (Revista de Direito Tributário Internacional Atual, 2017)
Common among several “aggressive” tax planning schemes used by MNEs is the fact that the negotiating structures undertaken by taxpayers relied, to some extent, on the unique features of the transfer pricing rules of the countries involved. In this context, BEPS Action 13 proposes the development of rules that may enhance transparency for tax administrations through the improvement and standardization of transfer pricing documentation. However, a tax administration is not free to use information obtained through the exchange or implementation of country-by-country reports in order to pursue its own means and goals, according to its tax policy. The authors suggest that the use of this information remains bound to the concept of “appropriate use” and that an improper use of the information may lead to improper results with regard to domestic tax assessments or the evaluation of the relevant aspects of legal facts.